An economic analysis on factors of oil palm production: a case study in Johor / Rossyafrieza Zulkahar - Zulkahar, Rossyafrieza (Faculty of Plantation and Agrotechnology, 2019)
Oil palm (Elaeis guineensis) is one of the major crops in Malaysia that contributes to the Malaysian economic. Malaysia contributes 39% of the world production and conquering 44% of world export. Oil palm industry contributing about RM69.3 billion to Malaysia’s GDPs in 2015. There are several factors that contribute to the oil palm production and this study highlighted on four factors which are the fertilizer, labours, rainfall distribution and technological application in the plantations. This research is focusing on studying the economic analysis on factors of oil palm production. The objective of this research is to study the economic analysis based on the factors as mentioned. Other than that, this study also was carried out to study the relationship between the factors affecting oil palm production. The study was done in two plantations in two different districts in Johor which are Ladang in Kota Tinggi and Ladang in Mersing district. The methodology used is interview and collecting secondary data from the companies. Then, the data were analysed using three analysis which are descriptive analysis, cost analysis and statistical analysis. The results show that Ladang in Mersing is more efficient in productivity compared to Ladang in Kota Tinggi due to the factors studied such as higher rainfall distribution and more technological application used. As the conclusion, all the factors highlighted are directly and indirectly affecting the production of oil palm. It was recommended that the plantations optimize each of the inputs used for a better production.